Sharia Fintech Innovation: Opportunities and Challenges in the Era of Economic Digitalization - Muhibban, Muhibban; Hasan, Nur (PT Elaborium Eevasi Indonesia, 2025)
The advancement of digital technology has significantly transformed the financial sector, including the emergence of financial technology (fintech) based on Sharia principles. This phenomenon underscores the importance of examining Sharia fintech innovations in addressing both the opportunities and challenges of the digital economy era. This paper aims to explore various forms of Sharia fintech innovations, analyze the opportunities they present, and identify the challenges involved in their implementation. The study employs a literature review approach, drawing on scholarly sources, industry reports, and regulatory documents related to Sharia-compliant fintech. The findings indicate that Sharia fintech models such as P2P lending, crowdfunding, e-wallets, and Sharia-based robo-advisory services hold significant potential for promoting financial inclusion and fostering a fair and sustainable financial ecosystem. However, several challenges persist, including low levels of Sharia financial literacy, competition with conventional fintech, and regulatory uncertainties. In conclusion, Sharia fintech represents an innovative solution for supporting a digital economy aligned with Islamic principles, yet its optimal development requires synergy among government bodies, industry stakeholders, and the broader society